2006
DOI: 10.4141/a05-056
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oil rich in polyunsaturated fatty acids for ruminants: Post-ruminal digesta characteristics and their implications on production

Abstract: . 2006. Dietary oil rich in polyunsaturated fatty acids for ruminants: Post-ruminal digesta characteristics and their implications on production. Can. J. Anim. Sci. 86: 159-170. Maximizing the production of ruminants requires high intakes of feeds that are energy dense, therefore feeds that are usually high in starch. Under these conditions there can be significant passage of partially digested feed starch and fibre to the small intestine. These digesta components interact in a manner that can diminish post-ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Other hypophagic effects of long-chain fatty acids, including reductions in digesta viscosity (Mir, McAllister, Gibb, & Okine, 2006) and gastrointestinal motility (Drackley, Klusmeyer, Trusk, & Clark, 1992), may have impaired feed intake. Both effects are associated with the secretion of cholecystokinin (CCK), a neuropeptide secreted from duodenal I cells that acts as a short-term regulator of feed intake (Gibbs, Smith, & Greenberg, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Other hypophagic effects of long-chain fatty acids, including reductions in digesta viscosity (Mir, McAllister, Gibb, & Okine, 2006) and gastrointestinal motility (Drackley, Klusmeyer, Trusk, & Clark, 1992), may have impaired feed intake. Both effects are associated with the secretion of cholecystokinin (CCK), a neuropeptide secreted from duodenal I cells that acts as a short-term regulator of feed intake (Gibbs, Smith, & Greenberg, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the choice of grain type, the preparation method [73] as well as maturity of grain at harvest are important [74]. Mature ground or rolled grain is recommended [75]. Rumen resistant starch may not be completely hydrolysed in the small intestine [76] due to starch increasing small intestine viscosity [75].…”
Section: Encourage Ovarian Cyclic Activitymentioning
confidence: 99%
“…Mature ground or rolled grain is recommended [75]. Rumen resistant starch may not be completely hydrolysed in the small intestine [76] due to starch increasing small intestine viscosity [75]. Therefore, the total starch level of the diet should be lower than 35-40% to avoid acidosis and allow complete starch hydrolysis [77].…”
Section: Encourage Ovarian Cyclic Activitymentioning
confidence: 99%
“…The benefits of dietary oils to ruminants are associated with an improvement of bioactive lipid components in ruminant products by alteration of the ruminal microbial population (Mir et al, 2006;SzumacherStrabel et al, 2011b). In this study, oil supplemented diets incubated for 24 hours in the batch culture system showed an increase in LCFA, UFA, MUFA and PUFA and a decrease in MCFA in the rumen fluid, regardless the diet composition.…”
Section: Diet Composition and Oil Supplementation In Relation To Fa Pmentioning
confidence: 99%